Insights into Components of Prospective Science Teachers' Mental Models and Their Preferred Visual Representations of Atoms - Aysegül Derman; Nuriye Koçak; Ingo Eilks (MDPI AG, 2019)
This study focused on determining the elements of mental models of atomic structure and views on visual representations of models of atomic structure in two sub-cohorts of student teachers studying at a university in Turkey. In total, 141 student teachers participated in this study. In the first cohort, the focus was on 73 freshman science student teachers’ drawings of mental models of atomic structure. The analysis showed a wide variety of individual aspects in the students’ minds when asked to sketch the structure of atoms. The majority of students preferred to draw two-dimensional structures, neglecting the atom’s space-filling character. Concerning the details of atomic structure, the majority of students emphasized only the most essential components of atoms, namely protons, neutrons, and electrons. It was quickly recognizable that these elements were arranged according to different analogies or representations of historical models, particularly related to Bohr’s atomic theory and different representations thereof. Overall, the different visual representations of atomic models the students see in school, almost exclusively serve as the basis for their ideas about atomic structure. Current atomic theory, like quantum mechanical models, are generally not used when students are asked for a “contemporary” model of atoms. Rather it seems that concreteness and functionality are the primary factors leading to the selection of an atomic model when requested. This study is supplemented by data collected from the second cohort of 68 prospective teachers consisting of a diverse group of students ranging from freshman to senior level. The students in this cohort were asked for their preferred illustrations of atoms in textbooks. Open-ended questions about atoms led to further insights. The analysis of the prospective teachers’ drawings indicated that a more careful approach to teaching is necessary to clarify the relationships between different models of atomic structure and to allow students to understand what an appropriate and contemporary understanding of atomic structure should encompass.